Performance of Serial Concatenated Convolutional Code with Dithered Golden Section Channel Interleaver over Frequency Selective Rayleigh Fading Channel - Z. AL-Macdici, Raghad (Journal of Engineering and Sustainable Development, 2005)
Serial concatenated convolutional coding with iterative decoding is examined for data transmission over the downlink of a WCDMA system employing BPSK modulation and coherent Rake receiver. Performance of serial concatenated convolutional coding is studied in a frequency selective Rayleigh fading channel. The new type of external interleaver which is called Dithered Golden section Interleaver (DGI) is used The effect of correlated fading on the performance of the proposed system is investigated by considering external block interleaver delays of 10 ms at mobile speeds 5 and 100 km/h. Simulation results show that the employing this type of interleaver is outperforming at high signal to noise ratios the structured interleaver (Block, circular …etc).